(3cGed GdUfGYJjf (B: (3GdHjWQI hGdRQObIs - (3YHO Gddg Hf GdHOQ GdHjWGQ GdeUQj, GHf GdefPQ, CHh HcQ , J (B741 (3g` s
(3ChdgG (B:s
(3deG QCjJ GdHjGWQI hGdCWHGA hGdRQGObI hGdadGSaI hGdMceGA bO JbOehG hVYhG cJHkG cKjQI ai Yde GdHjWQI hGdRQbI hGdYdGLGJ EdG Cfge de jHjfhG ajgG LejY GdCSHGH hGdYdGeGJ hGdCdhGf s
(3BNQgG (B:s
(3hCeG HbjI GdCQHYjf WQbI fYGd ade fHjf UaJge (B((3cPG(B) (3gGgfG dSHHjf (B: (3CMOgeG , GdEcKGQ hGdEedGd hGdKGfi adCfg de jcf dgG efaYI ai GdJfYjd hOaY GdeVGQ , hdcfgG ddJaGNQ Hjf GdHjGWQI hGdUfGY s
(3fSNI QGHYIs
(3hai GHJOGA cd ebGdI agQS HCHhGHgGs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B194 ; (3eLdI eYgO GdeNWhWGJ (B- (3GdLRA (B5 - (3U (B282 s
Keywords: (3GdWHs